Employing FAHP to de-codify the determinants of trade agreements: a case of the EU-India trade talks - Khorana, Sangeeta; Cho, Jaemin; Lee, Jaeho; Disegna, Marta (Technological and Economic Development of Economy, 2018)
This paper employs an interdisciplinary approach that combines economics with Fuzzy Analytic Hierarchy Process (FAHP) approach to de-codify the anatomy of free trade agreements (FTA) determinants focusing, in particular, on the case of EU-India FTA. The novelty of this paper is the systematic empirical analysis of the FTA determinants using FAHP. More than a hundred businesses and trade practitioners were interviewed in the EU and India to understand the lack of momentum in FTA talks. Our findings indicate that economic and political criteria are predominant FTA determinants, with market access potential (economic) as important factors driving the EU-India FTA talks. Given that results suggest similar perceptions of both the EU and India interview-ees to FTA determinants it is likely that the EU and India could find common ground and resume the languishing FTA negotiations.